The Relationship of Nurses' Knowledge with Implementation of Centralized Medication in Inpatient Room of Otanaha Regional Public Hospital, Gorontalo City - Rajawali, Sri Muliyani; Ilham, Rosmin; Syukur, Sabirin B. (Universitas Ibn Khaldun Bogor, 2024)
Introduction: Centralized medicine is medicine that will be given to patients where the management of the medicine is completely handed over to the nurse so that the use of medicine can be controlled. This study aimed to determine nurses' knowledge about the implementation of drug centralization in inpatient rooms P1 and P2. Exploratory descriptive method, the population in this study was all 106 nurses, a sample of 51 respondents using a purposive sampling technique. Data collection used a questionnaire sheet. This research was conducted at the Otanaha Regional General Hospital, Gorontalo City, with the research period from May to July 2023. The highest level of good knowledge was that 35 respondents (58.6%) had understood the application of drug centralization. The results of research regarding the relationship between nurses' knowledge and the application of drug centralization had a level of 95% confidence and up Chi-Square obtained a p-value of 0.000 which is smaller (p < a 0.05) which means there is a relationship between nurses' knowledge of the application of centralization. So it can be concluded that nurses' knowledge of the application of drug centralization is stated to have a significant level which means there is a relationship between the two variables.